Regularity of acoustic radiation at ascending load on a pair of friction from a composite material - Філоненко, С. Ф.; Космач, О. П.; Косицька, Т. М. (Proceedings of National Aviation University (archive), 2013)
In this article the simulation the results of acoustic emission signals formed by friction surfaces with composite materials at load increasing were showed. The results showed that at increase of axial load increases the amplitude of the resulting parameters of acoustic emission signals, such as the average amplitude, its standard deviation and variance. Thus were obtained the basic changes of amplitude parameters generated signals. Was determined that the variation of the percentage increase in the average amplitude, its standard deviation and variance were the same type of character, with well approximate by linear functions. The results showed that with growing of axial load the percent increase in average amplitude of the resulting acoustic emission signals. Also, an analysis of the energy parameters of acoustic emission with increasing axial load on the friction pair with composite materials was conducted. The simulation results showed that the percentage increase in the average level of energy and its standard deviation are approximate by linear functions. At the same time the greatest percentage increase with increasing axial load on the friction pair is observed in the dispersion of the average energy of the resulting acoustic emission signals. The results showed that at experimental study of the acoustic emission signals with increasing axial load on the friction pair with composite materials greatest growth is expected in the average amplitude of the resulting AE signals. The growth of its standard deviation and variance will be not significant. At the same time, the greatest growth is expected in the dispersion of the average energy of acoustic emission signals